Visual Art as a Means of Presenting a Fashion Designer’s Creative Idea - Людмила Дихнич (Культура і мистецтво у сучасному світі, 2023)
The aim of the article is to identify the types and functions of fashion graphics as a means of visualising the ideas and concepts of a fashion designer. Results. The role of visual art in expressing the idea of a fashion designer is characterised; based on the systematisation and analysis of examples of fashion graphics that visualise clothing models of such designers as K. Dior, Y. Saint Laurent, H. Mepen, V. Nesmiian, A. Tan, V. Anisimov, as well as the author’s graphics of K. Lagerfeld, the following types of using visual art in presenting designer’s ideas are identified 1) fashion illustration in suit presentation; 2) Illustrated fashion magazines; 3) fashion illustration as a design element of the designer’s publications and fashion publications; 4) sketch of the product; 5) generalised (conceptual) image of the collection; 6) narrative graphics. The research methods include analysis and synthesis, historical and chronological, comparative, figurative and stylistic analysis, selective method, and systematisation of visual information. Scientific novelty. For the first time, in the context of the history and contemporary development of the fashion system, examples of fashion illustrations, sketches, and drawings by foreign and Ukrainian artists and designers are considered in the context of the designer’s communication with the target audience; for the first time, models of Ukrainian designers from fashion magazines of the 1960s–1970s, as well as models from collections of contemporary Ukrainian designers, are introduced into scientific circulation. Conclusions. After analysing the goals of designers and the impact of visual works on promoting fashion and fixing the suit images in the imagination of the consumer audience, the following functions of fashion graphics are identified: communicative (by presenting a sketch or illustration, the designer establishes or reinforces a connection with the target audience); advertising (by placing a sketch, illustration or author’s narrative graphics in the information space — printed and online sources, the designer promotes a new product or creates cult features for an existing product); correspondence of the suit to a work of art (using visual means, the designer brings closer or equates the process of creating a suit with the creation of a work of visual art). The practical significance lies in identifying the functions of visual works that present the ideas of designers. The artistic work of artists and designers, which reveals the uniqueness of the created clothing examples, can still be used by designers today, both in the design process and as analogues of advertising and communication tools.